Phytoplankton enhances the flocculation of suspended particulate matter in a turbid estuary - Luz Amadei Martínez; Koen Sabbe; Michael Fettweis; Xavier Desmit; Yves Israel; Wout Bakker; Renaat Dasseville; Sofie D'hondt; Ilse Daveloose; Tine Verstraete; Peter Chaerle; Natacha Brion; et al. (Limnology and Oceanography, 2025)
Over the past decades, improvements in water quality—particularly increased oxygen and reduced nitrogen concentrations—have led to changes in phytoplankton biomass and community composition in the Schelde estuary, a macrotidal estuary in Belgium/SW Netherlands. We argue that these changes have affected SPM dynamics by modifying floc stability and size. Seasonal and spatial variability in SPM flocculation dynamics were examined using water samples collected monthly from December 2021 to December 2022 at five stations in the freshwater and brackish tidal reaches of the estuary. In a custom‐built flocculation chamber, these samples were first subjected to a high turbulent shear rate (45 s −1 ) to break the flocs, followed by a lower shear rate (20 s −1 ) that promoted aggregation for 120 min. Floc size distribution changes were analyzed to determine key flocculation parameters, in particular, equilibrium floc size ( D e ), and flocculation speed ( V f ). Using generalized additive models, we assessed the influence of seasonal, spatial, environmental, and biotic factors on D e and V f . Unlike in the brackish stations, the freshwater stations displayed clear seasonal patterns in flocculation dynamics, with D e and V f increasing in spring and summer. The strong positive correlations between D e , V f , and Chl a , as well as between V f and phytoplankton‐derived particulate organic carbon, suggest that phytoplankton plays a key role in the flocculation process. Transparent exopolymer particles (TEP), which because of their sticky properties can promote particle coagulation, were only weakly correlated with enhanced flocculation, suggesting that TEP properties may be affected by factors such as its specific composition, age, and remineralization.

Siliceous plankton flux and radiolarian community structure in the highly oligotrophic Ionian Sea (Eastern Mediterranean) – Imprints of climate variability - Marie Cueille; Taniel Danelian; Dimitra-Ioli Skouroliakou; Elisavet Skampa; Maria Triantaphyllou; Alexandra Gogou; Georgia Kambouri; Ioanna Stavrakaki; Koen Sabbe (Marine Micropaleontology, 2025)

Local and Regional, Not Latitudinal, Variation in Microclimate and Bedrock Shapes Moss‐Associated Diatom Communities in Greenland - Charlotte Goeyers; Bart Van de Vijver; Tyler J. Kohler; Elie Verleyen; Bjorn Tytgat; S. Robbert Gradstein; Koen Sabbe (Journal of Biogeography, 2025)
Aim Greenland is among the most rapidly changing regions on Earth, with climate change having a profound impact on its terrestrial ecosystems. Here, moss‐associated diatoms hold great potential as sensitive biological indicators to monitor responses to climate change, but their diversity, community structure and biogeography remain virtually unexplored. Our study, thus, aims to (1) explore the diversity and community structure of moss‐associated diatoms in Greenland and (2) assess the environmental and spatial variables driving their geographic distribution, establishing a baseline for their use as bio‐indicators of climate change. Location Greenland, spanning a gradient from high to subarctic regions. Taxon Moss‐associated diatoms (Bacillariophyta). Methods LM and SEM analysis was conducted on 175 terrestrial moss samples collected from preserved herbarium material and fresh samples (1988–2021) from high, low and subarctic localities in Greenland. Biogeographical distributions, biodiversity patterns and community structure were examined in relation to environmental and spatial factors using Kruskal–Wallis, Spearman's Rank, ordination, SIMPROF and variation partitioning analyses. Results A total of 544 diatom taxa (66 genera) were identified, with nearly half potentially new to science. Community structure was predominantly influenced by moisture, pH, conductivity and temperature. Local variation in microclimate and bedrock, thus, explained more variation in the diatom communities than latitude‐related environmental gradients. Surprisingly, temperature had a negative impact on diatom richness, probably due to its adverse effect on moisture, highlighting the vulnerability of Arctic moss diatoms to global warming. Main Conclusions This study provides the first comprehensive analysis of Greenland's moss‐associated diatoms, highlighting their high diversity and sensitivity to environmental changes. Our findings underscore their potential as indicators for monitoring climate change in the Arctic, with moisture, pH, conductivity and temperature being critical factors influencing their communities, laying the groundwork for future research and monitoring efforts.

A New Dawn for Protist Biogeography - Eveline Pinseel; Koen Sabbe; Elie Verleyen; Wim Vyverman (Global Ecology and Biogeography, 2024)
Aim Biogeographers have believed for a long time that the geographical distributions of protists are only determined by environmental conditions, because dispersal is not limited. During the past two decades, the field has come a long way to show that historical and spatial factors also significantly contribute to shaping protist distributions, calling for a reappraisal of our understanding of protist biogeography. Methods We review the current state‐of‐the‐art on the field of protist biogeography, highlighting several outstanding questions and opportunities. Our review brings together insights from different disciplines, ranging from morphology‐based research to environmental, population and speciation genomics. Results Protist communities harbour cosmopolitan and geographically restricted species and are shaped by both local environmental conditions and historical processes, yet the relative contributions of these patterns and processes likely differs depending on the geographic scale, protist lineage and the habitat that is being investigated. The field is ready to move beyond the decades‐long ubiquity versus (moderate) endemicity discourse and to instead ask why and where specific protist species and clades are more prone to widespread or restricted distributions. With the advent of next‐generation sequencing technologies, from whole‐genome sequencing to environmental and ancient DNA surveys, it is now possible to integrate insights from multiple lines of evidence and investigate protist communities, species and populations at an unprecedented scale and detail. Outlook To further advance the field, the protist community needs to focus on understudied habitats and protist lineages, study the impact of protist traits on biogeographical patterns, perform targeted field and experimental work to disentangle the processes that underlie protist biogeographies and expand and develop databases with sequence, trait, distributional and phylogenetic information of protists. Given that a good understanding of species boundaries is central to unravelling protist biogeography, it remains crucial to invest in polyphasic taxonomic research.

High-resolution temporal NDVI data reveal contrasting intratidal, spring-neap and seasonal biomass dynamics in euglenoid- and diatom-dominated biofilms - Dorian A. Bas; Koen Sabbe; Daphne van der Wal; Renaat Dasseville; Dimitri Van Pelt; Patrick Meire (Science of The Total Environment, 2024)

Harnessing the power of tidal flat diatoms to combat climate change - Jihae Park; Hojun Lee; Jana Asselman; Colin Janssen; Stephen Depuydt; Jonas De Saeger; Thomas Friedl; Koen Sabbe; Wim Vyverman; Catharina J. M. Philippart; Jaime Pitarch; Philippe M. Heynderickx; et al. (Critical Reviews in Environmental Science and Technology, 2024)

Nassellarian polycystine radiolarians observed in sediment traps from the southern Ionian Sea (Eastern Mediterranean) - Marie Cueille; Taniel Danelian; Koen Sabbe; Mathias Meunier; Elisavet Skampa; Maria Triantaphyllou; Alexandra Gogou (Revue de Micropaléontologie, 2024)

Pronounced Seasonal and Spatial Variability in Determinants of Phytoplankton Biomass Dynamics along a Near–Offshore Gradient in the Southern North Sea - Viviana Otero; Steven Pint; Klaas Deneudt; Maarten De Rijcke; Jonas Mortelmans; Lennert Schepers; Patricia Martin-Cabrera; Koen Sabbe; Wim Vyverman; Michiel Vandegehuchte; Gert Everaert (Journal of Marine Science and Engineering, 2023)
Marine phytoplankton biomass dynamics are affected by eutrophication, ocean warming, and ocean acidification. These changing abiotic conditions may impact phytoplankton biomass and its spatiotemporal dynamics. In this study, we used a nutrient–phytoplankton–zooplankton (NPZ) model to quantify the relative importance of the bottom-up and top-down determinants of phytoplankton biomass dynamics in the Belgian part of the North Sea (BPNS). Using four years (2014–2017) of monthly observations of nutrients, solar irradiance, sea surface temperature, chlorophyll-a, and zooplankton biomass at ten locations, we disentangled the monthly, seasonal, and yearly variation in phytoplankton biomass dynamics. To quantify how the relative importance of determinants changed along a near–offshore gradient, the analysis was performed for three spatial regions, i.e., the nearshore region ( 30 km). We found that, from year 2014 to 2017, the phytoplankton biomass dynamics ranged from 1.4 to 23.1 mg Chla m−3. Phytoplankton biomass dynamics follow a general seasonal cycle, as is the case in other temperate regional seas, with a distinct spring bloom (5.3–23.1 mg Chla m−3) and a modest autumn bloom (2.9–5.4 mg Chla m−3). This classic bimodal bloom pattern was not observed between 2003 and 2010 in the BPNS. The seasonal pattern was most expressed in the nearshore region. The relative contribution of factors determining phytoplankton biomass dynamics varied spatially and temporally. Throughout a calendar year, solar irradiance and zooplankton grazing were the most influential determinants in all regions, i.e., they jointly explained 38–65% of the variation in the offshore region, 45–71% in the midshore region, and 56–77% in the nearshore region. In the near- and midshore regions, nutrients were the greatest limit on phytoplankton production in the month following the spring bloom (44–55%). Nutrients were a determinant throughout the year in the offshore region (27–62%). During winter, sea surface temperature was a determinant in all regions (15–17%). By the high-resolution spatiotemporal analysis of the relative contributions of different determinants, this study contributes to a better mechanistic understanding of the spatiotemporal dynamics of phytoplankton biomass in the southern North Sea. This detailed understanding is anticipated to contribute to the definition of targeted management strategies for the BPNS and to support sustainable development in Belgium’s blue economy.

Long-term phytoplankton dynamics in the Zeeschelde estuary (Belgium) are driven by the interactive effects of de-eutrophication, altered hydrodynamics and extreme weather events - Luz Amadei Martínez; Koen Sabbe; Renaat Dasseville; Ilse Daveloose; Tine Verstraete; Sofie D'hondt; Frédéric Azémar; Akoko Claudine Sossou; Micky Tackx; Tom Maris; Patrick Meire; Wim Vyverman (Science of The Total Environment, 2023)

From Bacteria to Zooplankton: An Integrative Approach Revealing Regional Spatial Patterns During the Spring Phytoplankton Bloom in the Southern Bight of the North Sea - Anaïs Aubert; Olivier Beauchard; Reinhoud de Blok; Luis Felipe Artigas; Koen Sabbe; Wim Vyverman; Luz Amadei Martínez; Klaas Deneudt; Arnaud Louchart; Jonas Mortelmans; Machteld Rijkeboer; Elisabeth Debusschere (Frontiers in Marine Science, 2022)
Plankton comprises a large diversity of organisms, from pico- to macro-sized classes, and spans several trophic levels, whose population dynamics are characterized by a high spatio-temporal variability. Studies integrating multiple plankton groups, in respect to size classes and trophic levels, are still rare, which hampers a more thorough description and elucidation of the full complexity of plankton dynamics. Here, we present a study on the spatial variability of five in-situ monitored plankton components, ranging from bacteria to meso-zooplankton, and using a complementary set of molecular, chemical and imaging tools, with samples obtained during the phytoplankton spring bloom in the hydrodynamically complex Southern Bight of the North Sea. We hypothesized that while generally recognized spatial gradients in e.g. salinity, turbidity and nutrients will have a strong impact on plankton spatial distribution patterns, interactions within the plankton compartment but also lag effects related to preceding bloom-related events will further modulate spatial structuring of the plankton. Our study indeed revealed an overriding imprint of regional factors on plankton distribution patterns. The dominant spatial pattern mainly reflected regional differences in dissolved inorganic nutrients and particulate matter concentrations related to differences in phytoplankton bloom timing between the two main regions of freshwater influence, the Thames and the Scheldt-Rhine-Meuse. A second major pattern corresponded to the expected nearshore-offshore gradient, with increasing influence of low turbidity and low nutrient Atlantic waters in the offshore stations. Environmental forcing on specific plankton groups and inter-plankton relationships also appeared to drive plankton distribution. Although the marine plankton comprises heterogeneous functional groups, this study shows that multiple planktonic ecosystem components can be parts of common spatial gradients and that often neglected small planktonic organisms can be key drivers of such gradients. These analytical outcomes open questions on regional and seasonal reproducibility of the highlighted gradients.

Optical Detection of Harmful Algal Blooms in the Belgian Coastal Zone: A Cautionary Tale of Chlorophyll c3 - Alexandre Castagna; Heidi Dierssen; Emanuele Organelli; Margarita Bogorad; Jonas Mortelmans; Wim Vyverman; Koen Sabbe (Frontiers in Marine Science, 2021)
Phaeocystis globosa is a nuisance haptophyte species that forms annual blooms in the southern North Sea and other coastal waters. At high biomass concentration, these are considered harmful algal blooms due to their deleterious impact on the local ecosystems and economy, and are considered an indicator for eutrophication. In the last two decades, methods have been developed for the optical detection and quantification of these blooms, with potential applications for autonomous in situ or remote observations. However, recent experimental evidence suggests that the interpretation of the optical signal and its exclusive association with P. globosa may not be accurate. In the North Sea, blooms of P. globosa are synchronous with those of the diatom Pseudo-nitzschia delicatissima , another harmful bloom-forming species with similar pigmentation and optical signature. Here we combine new and published measurements of pigmentation composition and inherent optical properties from pure cultures of several algal and cyanobacterial groups, together with environmental spectroscopy data, to identify the pigments generating the optical signals captured by two established algorithms. We further evaluate the association of those pigments and optical signals with P. globosa . We found that the interpretation of the pigment(s) generating the optical signals were incorrect and that previous methods are not specific to P. globosa , even in the context of the phytoplankton assemblage of the southern North Sea. Additionally, we found that the optical and pigment signatures of Phaeocystis species are part of a broad pigmentation trend across unrelated taxonomic groups related to chlorophyll c 3 presence, with important consequences for the interpretation of pigment and optical data. We then develop and evaluate an algorithm to detect this pigmentation pattern with minimal influence of co-occurring species and elaborate general recommendations for the future development of algorithms.

Biodegradable, metal-chelating compounds as alternatives to EDTA for cultivation of marine microalgae - Justine Sauvage; Gary H. Wikfors; Koen Sabbe; Nancy Nevejan; Steven Goderis; Philippe Claeys; Xiaoxu Li; Alyssa Joyce (Journal of Applied Phycology, 2021)
Iron (Fe) is an essential nutrient for microalgal metabolism. The low solubility of Fe in oxic aquatic environments can be a growth-limiting factor for phytoplankton. Synthetic chelating agents, such as ethylenediaminetetraacetic acid (EDTA), are used widely to maintain Fe in solution for microalgal cultivation. The non-biodegradable nature of EDTA, combined with sub-optimal bioavailability of Fe-EDTA complexes to microalgae, indicates opportunity to improve microalgal cultivation practices that amplify production efficiency and environmental compatibility. In the present study, the effects of four organic chelating ligands known to form readily bioavailable organic complexes with Fe in natural aquatic environments were investigated in relation to growth and biochemical composition of two marine microalgae grown as live feeds in shellfish hatcheries ( Chaetoceros calcitrans and Tisochrysis lutea ). Three saccharides, alginic acid (ALG), glucuronic acid (GLU), and dextran (DEX), as well as the siderophore desferrioxamine B (DFB), were compared to EDTA. Organic ligands characterized by weaker binding capacity for cationic metals (i.e., ALG, GLU, DEX) significantly improved microalgal growth and yields in laboratory-scale static batch cultures or bubbled photobioreactors. Maximal microalgal growth enhancement relative to the control (e.g., EDTA) was recorded for GLU, followed by ALG, with 20–35% increase in specific growth rate in the early stages of culture development of C. calcitrans and T. lutea . Substitution of EDTA with GLU resulted in a 27% increase in cellular omega 3-polyunsaturetd fatty acid content of C. calcitrans and doubled final cell yields. Enhanced microalgal culture performance is likely associated with increased intracellular Fe uptake efficiency combined with heterotrophic growth stimulated by the organic ligands. Based upon these results, we propose that replacement of EDTA with one of these organic metal-chelating ligands is an effective and easily implementable strategy to enhance the environmental compatibility of microalgal cultivation practices while also maximizing algal growth and enhancing the nutritional quality of marine microalgal species commonly cultured for live-feed applications in aquaculture.

Light Regulation of LHCX Genes in the Benthic Diatom Seminavis robusta - Lander Blommaert; Emmelien Vancaester; Marie J. J. Huysman; Cristina M. Osuna-Cruz; Sofie D’hondt; Johann Lavaud; Bernard Lepetit; Per Winge; Atle M. Bones; Klaas Vandepoele; Wim Vyverman; Koen Sabbe (Frontiers in Marine Science, 2020)

Changes in chlorophyll concentration and phenology in the North Sea in relation to de‐eutrophication and sea surface warming - Xavier Desmit; Anja Nohe; Alberto Vieira Borges; Theo Prins; Karien De Cauwer; Ruth Lagring; Dimitry Van der Zande; Koen Sabbe (Limnology and Oceanography, 2020)
At least two major drivers of phytoplankton production have changed in recent decades in the North Sea: sea surface temperature (SST) has increased by ~ 1.6°C between 1988 and 2014, and the nitrogen and phosphorus loads from surrounding rivers have decreased from the mid‐1980s onward, following reduction policies. Long time series spanning four decades (1975–2015) of nutrients, chlorophyll (Chl), and pH measurements in the Southern and Central North Sea were analyzed to assess the impact of both the warming and the de‐eutrophication trends on Chl. The de‐eutrophication process, detectable in the reduction of nutrient river loads to the sea, caused a decrease of nutrient concentrations in coastal waters under riverine influence. A decline in annual mean Chl was observed at 11 out of 18 sampling sites (coastal and offshore) in the period 1988–2016. Also, a shift in Chl phenology was observed around 2000, with spring bloom formation occurring earlier in the year. A long time series of pH in the Southern North Sea showed an increase until the mid‐1980s followed by a rapid decrease, suggesting changes in phytoplankton production that would support the observed changes in Chl. Linear correlations, however, did not reveal significant relationships between Chl variability and winter nutrients or SST at the sampling sites. We propose that the observed changes in Chl (annual or seasonal) around 2000 are a response of phytoplankton dynamics to multiple stressors, directly or indirectly influenced by de‐eutrophication and climate warming.

Seasonal changes in the biochemical fate of carbon fixed by benthic diatoms in intertidal sediments - Tanja C. W. Moerdijk‐Poortvliet; Peter van Breugel; Koen Sabbe; Olivier Beauchard; Lucas J. Stal; Henricus T. S. Boschker (Limnology and Oceanography, 2018)
Benthic diatoms are important primary producers in intertidal marine sediments and form the basis of the food web in these ecosystems. In order to investigate the carbon flow within diatom mats, we performed in situ 13 C pulse‐chase labeling experiments and followed in detail the biochemical fate of carbon fixed by the diatoms for five consecutive days. These labeling experiments were done at approximately 2‐monthly intervals during 1 yr in order to cover seasonal variations. The fixed carbon was recovered in individual carbohydrates including extracellular polymeric substances (EPS), amino acids, fatty acids, and nucleic acid bases. In addition, we assessed a variety of environmental parameters and photosynthetic characteristics. The fixed carbon was initially mainly stored as carbohydrate (glucose) while nitrogen‐rich compounds (e.g., amino acids and RNA/DNA) were produced more slowly. During the year, the diatoms distributed the photosynthetically fixed carbon differently among the various carbon pools that were measured. In summer, the diatoms decreased carbon fixation and accumulated relatively more lipid as a storage compound (27% ± 2% vs. 12% ± 5% in other seasons). The percentage of fixed carbon that was excreted as EPS was lower in summer compared to other seasons, amounting 9% ± 4% and 21% ± 6%, respectively. Hence, it seemed that the physiology of the microphytobenthos was different during summer and caused by higher light intensity and a shift in nitrogen source.

Contrasting NPQ dynamics and xanthophyll cycling in a motile and a non‐motile intertidal benthic diatom - Lander Blommaert; Marie J. J. Huysman; Wim Vyverman; Johann Lavaud; Koen Sabbe (Limnology and Oceanography, 2017)
Diatoms living in intertidal sediments have to be able to rapidly adjust photosynthesis in response to often pronounced changes in light intensity during tidal cycles and changes in weather conditions. Strategies to deal with oversaturating light conditions, however, differ between growth forms. Motile epipelic diatoms can migrate to more optimal light conditions. In contrast, non‐motile epipsammic diatoms appear to mainly rely on higher Non‐Photochemical Quenching (NPQ) of chlorophyll a fluorescence to dissipate excess light energy, and this has been related to a larger pool of xanthophyll cycle (XC) pigments. We studied the effect of 1 h high Photosynthetically Available Radiation (PAR) (2000 μmol photons m −2 s −1 ) on the kinetics of the xanthophyll cycle and NPQ in both a motile diatom ( Seminavis robusta ) and a non‐motile diatom ( Opephora guenter‐grassii ) in an experimental set‐up which did not allow for vertical migration. O. guenter‐grassii could rapidly switch NPQ on and off by relying on fast XC kinetics. This species also demonstrated high de novo synthesis of xanthophylls within a relatively short period of time (1 h), including significant amounts of zeaxanthin, a feature not observed before in other diatoms. In contrast, S. robusta showed slower NPQ and associated XC kinetics, partly relying on NPQ conferred by de novo synthetized diatoxanthin molecules and synthesis of Light‐Harvesting Complex X (LHCX) isoforms. Part of this observed NPQ increase, however, is sustained quenching (NPQs). Our data illustrate the high and diverse adaptive capacity of microalgal growth forms to maximize photosynthesis in dynamic light environments.

Biodiversity increases functional and compositional resistance, but decreases resilience in phytoplankton communities - Jan M. Baert; Frederik De Laender; Koen Sabbe; Colin R. Janssen (Ecology, 2016)
There is now ample evidence that biodiversity stabilizes aggregated ecosystem functions, such as primary production, in changing environments. In primary producer systems, this stabilizing effect is found to be driven by higher functional resistance (i.e., reduced changes in functions by environmental changes) rather than through higher functional resilience (i.e., rapid recovery following environmental changes) in more diverse systems. The stability of aggregated ecosystem functions directly depends on changes in species composition and by consequence their functional contributions to ecosystem functions. Still, it remains only theoretically explored how biodiversity can stabilize ecosystem functions by affecting compositional stability. Here, we demonstrate how biodiversity effects on compositional stability drive biodiversity effects on functional stability in diatom communities. In a microcosm experiment, we exposed 39 communities of five different levels of species richness (1, 2, 4, 6, and 8 species) to three concentrations of a chemical stressor (0, 25, and 250 μg/L atrazine) for four weeks, after which all communities were transferred to atrazine‐free medium for three more weeks. Biodiversity simultaneously increased, increasing functional and compositional resistance, but decreased functional and compositional resilience. These results confirm the theoretically proposed link between biodiversity effects on functional and compositional stability in primary producer systems, and provide a mechanistic underpinning for observed biodiversity–stability relationships. Finally, we discuss how higher compositional stability can be expected to become increasingly important in stabilizing ecosystem functions under field conditions when multiple environmental stressors fluctuate simultaneously.

Release of dissolved carbohydrates by E miliania huxleyi and formation of transparent exopolymer particles depend on algal life cycle and bacterial activity - Nicolas Van Oostende; Tanja C. W. Moerdijk‐Poortvliet; Henricus T. S. Boschker; Wim Vyverman; Koen Sabbe (Environmental Microbiology, 2013)
Summary The coccolithophore E miliania huxleyi plays a pivotal role in the marine carbon cycle. However, we have only limited understanding of how its life cycle and bacterial interactions affect the production and composition of dissolved extracellular organic carbon and its transfer to the particulate pool. We traced the fate of photosynthetically fixed carbon during phosphate‐limited stationary growth of non‐axenic, calcifying E . huxleyi batch cultures, and more specifically the transfer of this carbon to bacteria and to dissolved high molecular weight neutral aldoses ( HMW NAld ) and extracellular particulate carbon. We then compared the dynamics of dissolved carbohydrates and transparent exopolymer particles ( TEP ) between cultures of non‐axenic and axenic diploid E . huxleyi . In addition, we present the first data on extracellular organic carbon in (non‐axenic) haploid E . huxleyi cultures. Bacteria enhanced the accumulation of dissolved polysaccharides and altered the composition of dissolved HMW NAld , while they also stimulated the formation of TEP containing high densities of charged polysaccharides in diploid E . huxleyi cultures. In haploid E . huxleyi cultures we found a more pronounced accumulation of dissolved carbohydrates, which had a different NAld composition than the diploid cultures. TEP formation was significantly lower than in the diploid cultures, despite the presence of bacteria. In diploid E . huxleyi cultures, we measured a high level of extracellular release of organic carbon (34–76%), retrieved mainly in the particulate pool instead of the dissolved pool. Enhanced formation of sticky TEP due to bacteria–alga interactions, in concert with the production of coccoliths, suggests that especially diploid E . huxleyi blooms increase the efficiency of export production in the ocean during dissolved phosphate‐limited conditions.

Lack of population genetic structuring in the marine planktonic diatom Pseudo-nitzschia pungens (Bacillariophyceae) in a heterogeneous area in the Southern Bight of the North Sea - Griet Casteleyn; Katharine M. Evans; Thierry Backeljau; Sofie D’hondt; Victor A. Chepurnov; Koen Sabbe; Wim Vyverman (Marine Biology, 2009)

The Belgian sandy beach ecosystem: a review - Jeroen Speybroeck; Dries Bonte; Wouter Courtens; Tom Gheskiere; Patrick Grootaert; Jean‐Pierre Maelfait; Sam Provoost; Koen Sabbe; Eric W. M. Stienen; Vera Van Lancker; Wouter Van Landuyt; Magda Vincx; et al. (Marine Ecology, 2008)
This paper reviews the available knowledge on sedimentology, hydrodynamics and five major ecosystem components (microphytobenthos, vascular plants, terrestrial arthropods, zoobenthos, and avifauna) of Belgian sandy beaches. It covers the area from the foredunes to the lower foreshore, takes an ecosystem approach to beaches of this specific geographic area. Morphodynamically, Belgian beaches are (ultra‐)dissipative, macrotidal, and wide. Characteristic grain sizes are 160–380 μm. The sand becomes coarser, beach slopes steeper and tidal range smaller towards the south‐west, where beaches have also been frequently reshaped by human interference such as nourishment. Beach organisms are highly adapted to this unique environment and can reach high numbers. We show that even on a heavily populated coastline subjected to intense recreational and development pressure, beaches provide critical, yet threatened, habitats. Vascular plants growing near the drift line, on the dry beach and in the embryonic dunes are mostly short‐lived and thalassochorous; the most common species include sea rocket ( Cakile maritima ), prickly saltwort ( Salsola kali subsp. kali ), and sea sandwort ( Honckenya peploides ). These zones are habitat to a highly diverse suite of terrestrial arthropods of halobiontic, halophilous and haloxene species; prominent members are sandhoppers ( Talitrus saltator ) and dipterans (flies). Microphytobenthos, mainly diatoms, is an important primary producer on Belgian beaches but is not well known. The meio‐ and macrobenthos of Belgian beaches contains specific assemblages such as the Scolelepis squamata–Eurydice pulchra community of the upper intertidal zone. Birds no longer nest on the beaches itself, but Belgian sandy shores continue to function as important resting and foraging areas for birds such as the sanderling Calidris alba . We identify several human pressures on the beach ecosystems arising from recreation, beach management and fisheries.

Late Quaternary climatic changes in southern Chile, as recorded in a diatom sequence of Lago Puyehue (40°40′ S) - Mieke Sterken; Elie Verleyen; Koen Sabbe; Griet Terryn; Francois Charlet; Sébastien Bertrand; Xavier Boës; Nathalie Fagel; Marc De Batist; Wim Vyverman (Journal of Paleolimnology, 2008)

Late Holocene changes in ultraviolet radiation penetration recorded in an East Antarctic lake - Elie Verleyen; Dominic A. Hodgson; Koen Sabbe; Wim Vyverman (Journal of Paleolimnology, 2005)

Quantifying habitat‐specific diatom production: A critical assessment using morphological and biogeochemical markers in Antarctic marine and lake sediments - Elie Verleyen; Dominic A. Hodgson; Peter R. Leavitt; Koen Sabbe; Wim Vyverman (Limnology and Oceanography, 2004)
Reconstructions of historical primary production, and of the algal groups and habitats that contribute to it, are fundamental in studies of climate and environmental change in both marine and freshwater environments. The aims of this study were to critically evaluate morphological and biogeochemical markers of diatom production by direct comparison of diatom marker pigments with absolute diatom biovolume and to partition diatom production between the main habitats (plankton, sea ice, and benthos). Sediments in two cores from the Larsemann Hills, Antarctica, spanning the last 10,000 yr, were analyzed for siliceous microfossils by microscopy and for fossil pigments by high‐performance liquid chromatography. Diatom pigments (diadinoxanthin, diatoxanthin, fucoxanthin) were highly correlated ( r 2 = 0.557 and 0.358, p r 2 = 0.102, p = 0.111; r 2 = 0.223, p = 0.001, after correction for temporal autocorrelation), possibly because of frustule dissolution and selective degradation of diadinoxanthin and diatoxanthin. In contrast, fucoxanthin was better preserved. By combining both microfossil and pigment proxies, we obtained a first estimate of diatom production in specific habitats (benthic and planktonic). Benthic diatom production was greatest in the lacustrine core sections, when benthic microbial mats dominated the flora, whereas diatoms were associated mainly with the water column and sea ice during the marine intervals. The combination of both proxies in marine and freshwater environments permits more accurate interpretation of pigment and diatom data in paleo‐ and neoecological research and the partitioning of diatom production between habitats.

Late Quaternary deglaciation and climate history of the Larsemann Hills (East Antarctica) - Elie Verleyen; Dominic A. Hodgson; Koen Sabbe; Wim Vyverman (Journal of Quaternary Science, 2004)
The Late Quaternary climate history of the Larsemann Hills has been reconstructed using siliceous microfossils (diatoms, chrysophytes and silicoflagellates) in sediment cores extracted from three isolation lakes. Results show that the western peninsula, Stornes, and offshore islands were ice‐covered between 30 000 yr BP and 13 500 cal. yr BP. From 13 500 cal. yr BP (shortly after the Antarctic Cold Reversal) the coastal lakes of the Larsemann Hills were deglaciated and biogenic sedimentation commenced. Between 13 500 and 11 500 cal. yr BP conditions were warmer and wetter than during the preceding glacial period, but still colder than today. From 11 500 to 9500 cal. yr BP there is evidence for wet and warm conditions, which probably is related to the early Holocene climate optimum, recorded in Antarctic ice cores. Between 9500 and 7400 cal. yr BP dry and cold conditions are inferred from high lake‐water salinities, and low water levels and an extended duration of nearshore sea‐ice. A second climate optimum occurred between 7400 and 5230 cal. yr BP when stratified, open water conditions during spring and summer characterised the marine coast of Prydz Bay. From 5230 until 2750 cal. yr BP sea‐ice duration in Prydz Bay increased, with conditions similar to the present day. A short return to stratified, open water conditions and a reduction in nearshore winter sea‐ice extent is evident between 2750 and 2200 cal. yr BP. Simultaneously, reconstructions of lake water depth and salinity suggests relatively humid and warm conditions on land between 3000 and 2000 cal. yr BP, which corresponds to a Holocene Hypsithermal reported elsewhere in Antarctica. Finally, dry conditions are recorded around 2000, between 760 and 690, and between 280 and 140 cal. yr BP. These data are consistent with ice‐core records from Antarctica and support the hypothesis that lacustrine and marine sediments on land can be used to evaluate the effect of long‐term climate change on the terrestrial environment. Copyright © 2004 John Wiley & Sons, Ltd.

Evidence for constant and highly specific active food selection by benthic ciliates in mixed diatoms assemblages - Ilse Hamels; Heidi Mussche; Koen Sabbe; Koenraad Muylaert; Wim Vyverman (Limnology and Oceanography, 2004)
Observational and experimental studies have shown that phagotrophic ciliates are highly selective predators. However, little is as yet known about the actual mechanisms involved in prey selection. We used direct behavioral observations to study the mechanism of prey selection in benthic algivorous ciliates feeding on mixed assemblages of diatom species. Four ciliate species, viz. three Strombidium species and a Pseudochilodonopsis species, and three diatom species from intertidal sediments in the Schelde estuary were used for the experiments. In each experiment, a single ciliate species was offered a mixture of two diatom species. The feeding preferences of the ciliates were estimated as well as relative encounter rates, attack probabilities, and capture successes for the prey species. The feeding preferences of the ciliates were distinctly predatorߚspecific and highly discerning with respect to the nature of the prey species. They appeared to result mainly from active selection at the time of the encounters and between the encounter and attack of the diatoms. Our observations suggest that selective encounters with the diatoms were caused by noncontact detection of individual prey items, at least for the Strombidium species. Additional experiments confirmed that these ciliates were able to distinguish between diatom species on the basis of soluble chemical cues. Grazing was also constant, i.e., prey switching was not observed. Moreover, neither total prey density nor feeding history influenced the preferences. We hypothesize that these highly specialized trophic interactions may be an important driving force in shaping structure and diversity of benthic diatom communities in intertidal sediments.

New species of Fragilariforma (Bacillariophyceae) from New Zealand and Australia - Cathy Kilroy; Koen Sabbe; Elizabeth A. Bergey; Wim Vyverman; Rex Lowe (New Zealand Journal of Botany, 2003)
Two new species of Fragilariforma, F. cassieae sp. nov. and F. rakiuriensis sp. nov., are described from material from New Zealand, with reference to populations found in Australia. The new species are similar in shape and size to Fragilariforma lata and F. hungarica var. tumida but are separated on the basis of areola and stria density, and shape. The distinguishing features of F. cassieae are a rhombic shape with narrow protracted ends, and striae with prominent areolae. In F. rakiuriensis, small forms are similar in shape to F. cassieae, but larger cells are elongated with a constriction at the centre. The striae are more widely spaced than in F. cassieae with a slightly irregular appearance and fine, closely spaced areolae. We discuss the relationships of the new species within the genus Fragilariforma, and also discuss the possible existence of further related taxa in the material examined, or marked shifts in form in their morphological progression during cell division. The two species described represent further evidence of a higher degree of endemism in Southern Hemisphere freshwater diatoms, and particularly in New Zealand and Australia, than has previously been assumed.

Modelling diatom responses to climate induced fluctuations in the moisture balance in continental Antarctic lakes - Elie Verleyen; Dominic A. Hodgson; Wim Vyverman; Donna Roberts; Andrew McMinn; Koenraad Vanhoutte; Koen Sabbe (Journal of Paleolimnology, 2003)

Zooplankton, phytoplankton and the microbial food web in two turbid and two clearwater shallow lakes in Belgium - Koenraad Muylaert; Steven Declerck; Vanessa Geenens; Jeroen Van Wichelen; Hanne Degans; Jochen Vandekerkhove; Katleen Van der Gucht; Nele Vloemans; Wouter Rommens; Danny Rejas; Roberto Urrutia; Koen Sabbe; et al. (Aquatic Ecology, 2003)

Dynamics and trophic roles of heterotrophic protists in the plankton of a freshwater tidal estuary - Koenraad Muylaert; Riet Van Mieghem; Koen Sabbe; Micky Tackx; Wim Vyverman (Hydrobiologia, 2000)